2019
DOI: 10.1186/s12918-019-0706-y
|View full text |Cite
|
Sign up to set email alerts
|

How to schedule VEGF and PD-1 inhibitors in combination cancer therapy?

Abstract: BackgroundOne of the questions in the design of cancer clinical trials with combination of two drugs is in which order to administer the drugs. This is an important question, especially in the case where one agent may interfere with the effectiveness of the other agent.ResultsIn the present paper we develop a mathematical model to address this scheduling question in a specific case where one of the drugs is anti-VEGF, which is known to affect the perfusion of other drugs. As a second drug we take anti-PD-1. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…In the clinical use, different agents of combination therapies may have different administration schedules due to their respective mechanisms of action and pharmacokinetics, which can increase the burden on medical staff and patients. The simultaneous administration observed to be effective here may be more straightforward and clinically translatable than other described combinations that may require the administration of dual drugs on different schedules (51)(52)(53).…”
Section: Discussionmentioning
confidence: 94%
“…In the clinical use, different agents of combination therapies may have different administration schedules due to their respective mechanisms of action and pharmacokinetics, which can increase the burden on medical staff and patients. The simultaneous administration observed to be effective here may be more straightforward and clinically translatable than other described combinations that may require the administration of dual drugs on different schedules (51)(52)(53).…”
Section: Discussionmentioning
confidence: 94%
“…However, some studies have reported that better results can be achieved by ICB therapy rst. [27]. Together, Optimal dose and schedule selection for combined antiangiogenic and ICB therapy in clinical trials will be critical.…”
Section: Discussionmentioning
confidence: 99%
“…Using a continuum, multiscale mechanistic model of drug PK/PD, integrated with tumor growth dynamics, Dogra et al performed virtual (i.e., in silico) clinical trials and identified drug synergism between the PD-L1 inhibitor atezolizumab and nanoparticle-based microRNA-22 therapy in triple negative breast cancer (Dogra et al, 2022). Similarly, Lai et al developed a PDE-based model and simulated the temporal dynamics of vascular tumor growth and immune interactions to optimize the scheduling of anti-VEGF and anti-PD-1 combination therapy (Lai & Friedman, 2019). Their modeling analyses suggested improved treatment outcomes with nonsimultaneous administration of the two therapies, with anti-PD-1 preceding anti-VEGF.…”
Section: Mechanistic Modelsmentioning
confidence: 99%